Making sense out of suffering: James 1:2-4 - Wolmarans, J. L. P. (Hervormde teologiese studies, 1991)
The logic of James 1:2-4 is examined. The argument is viewed as a syllogism, with the demonstrandum: ‘The believer who experiences trials must be happy.’ The proof of the argument runs as follows: »If there are trials, then there is testing ( = refining) of faith. » If there is testing ( = refining) of faith, then there is endurance in faith. It there is endurance in faith, then there must be perfect works. »If there are perfect works, then a perfect character develops. If there is a perfect character, then each virtue is possessed and each fully developed. »If each virtue is possessed and each fully developed, then the believer will receive the crown of life. »If the believer is to receive the crown of life, he will be happy.